Fretting fatigue under variable amplitude loading - Hooper, J. (Cranfield University, 2003)
Fretting fatigue is a major concern in the design of engineering components that will be subjected to clamping pressures whilst operating in a vibrational environment. The type of loading environment generated in these applications is generally of a variable amplitude nature. Therefore it is important for engineers to understand how such loading affects the severity of fretting fatigue. In the absence of this understanding, engineering designers are left to apply simplistic plain fatigue life prediction rules, such as Miners linear damage law, to try to estimate the damage generated from a particular loading history. In order to try to establish a baseline for the understanding of fretting fatigue under variable amplitude loading, a structured series of CAL and V AL tests were designed and carried out. The aim of the CAL tests was to characterise the fretting fatigue test rig (designed by the author) so that an experimental foundation could be developed, upon which the fretting fatigue study was based. A structured investigation into the effects on fretting fatigue of applying various specifically designed loading histories was carried out and some very distinct relationships between the applied loading spectra and fretting fatigue life were found. For the application of overloads it was observed that overload size, overload application interval and the number of overloads in each application all had a sizeable effect on the severity of fretting. Two-level, three-level and five-level block loading tests were also investigated and numerous loading history dependent results were obtained. The applicability of Miners law to fretting fatigue was assessed. Combining Miners law with well-defined CAL stress-life results gave reasonable predictions for all of the V AL fretting fatigue tests carried out, with damage summations at failure ranging from 0.64 (non-conservative) to 3.19 (conservative). However, a more detailed investigation into the relationship between fretting fatigue lives and damage summations due to the individual loading levels highlighted that the assumption of linear damage may not be applicable to fretting fatigue, especially during crack initiation and early crack growth. A hypothesis was proposed to explain the fretting fatigue life and Miner damage results observed for the different loading spectra, and reasonable success was obtained for tests where the Miners law proved conservative (in 27 of 36 tests), although the hypothesis was not able to explain the non-conservative results obtained in the other nine tests.